Challenging Placelessness: Site-Specific Art within the Gallery - Lyons, Shannon Jade (Curtin University, 2015)
This practice-led research project investigates ways of challenging contemporary notions of placelessness through the production and installation of site-specific artworks within art gallery spaces. By focusing on the material, architectural, atmospheric and institutional conditions specific to art gallery spaces, and producing artworks that may reveal, expose and illuminate these conditions, the project aims to explore alternatives to the production of artwork in one place and its exhibition in another, and to the use of the art gallery as a ‘non-place’.